The role of artistic collaborations: selected comparisons from South African print studios and 'double act' artist collaborations - Bingham, Niall B (My University, 2016)
Collaboration in South African printmaking studios, both between artists and printmakers, and between artists working together in print studios are examined in this study. How South African artists have used the conventions of collaborative printmaking practices to complement their own practice; and what kind of dynamics can emerge from such collaborations is the primary concern of this study. Printmaking is widely viewed as a subsidiary, or supplementary practice to artists’ primary concerns in their particular medium of practice. It is important to examine the role of collaboration in printmaking studios, and how it may benefit, or hinder artists in their creative productions. To contextualise my study, I provide a brief historical overview of collaboration in Western printmaking; and briefly examine printmaking against South Africa’s political landscape since the 1960s. Recent critical observations on collaboration in the arts are introduced to foreground various categorizations and approaches to such practices. My research focus is not on the intricacies of collectivism in collaboration but rather on how a form of ‘teamwork’ collaboration in print studios can generate agency, within the context of concerns raised in my own creative practice. As a printmaking teacher, practitioner and collaborator, I hope these findings could be used to address some of the concerns experienced in collaborations.
A dissertation presented to the Faculty of Humanities of the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Arts in Fine Arts. Johannesburg, 2016
Keywords: Artists--South Africa; Arts--South Africa; Artistic collaboration